(untitled) (CIPEEX, 2022)
EXPOSURE TO AIR POLLUTION IS ASSOCIATED WITH SEVERAL NEGATIVE IMPACTS ON HUMAN HEALTH, BUT THERE IS STILL LITTLE EVIDENCE ON ITS IMPACTS ON MENTAL HEALTH. THIS WORK ANALYZED THE SCIENTIFIC EVIDENCE ON THE EFFECTS OF EXPOSURE TO AIR POLLUTANTS AND THEIR IMPACTS ON MENTAL HEALTH IN A SERIES OF THE LAST 10 YEARS. THE METHODOLOGY USED WAS A SYSTEMATIC REVIEW OF THE LITERATURE, FOLLOWING THE RECOMMENDATIONS OF THE PRISMA GUIDE (PREFERRED REPORTING ITEMS FOR SYSTEMATIC REVIEWS AND META-ANALYSES), IN TWO ELECTRONIC DATABASES (SCOPUS, AND WEB OF SCIENCE) WITH THE KEYWORDS "AIR POLLUTION" AND "MENTAL HEALTH", BETWEEN 1.1.2012 TO 07.26.2022. A TOTAL OF 2,362 ARTICLES WERE IDENTIFIED, OF WHICH 56 WERE SELECTED FOR ANALYSIS. ANXIETY AND DEPRESSION DISORDERS WERE THE TYPES OF PSYCHOLOGICAL IMPACTS MOST EVALUATED IN THE SURVEYS. THE MOST STUDIED POPULATIONS WERE CHILDREN, YOUNG PEOPLE AND THE ELDERLY. THE NEGATIVE AND INCREASINGLY INTENSE ASSOCIATION OF EXPOSURE TO POLLUTED AIR WITH MENTAL HEALTH OUTCOMES WAS EVIDENT.